2018
DOI: 10.1111/jopy.12379
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous orientation predicts longevity: New findings from the Nun Study

Abstract: Objective: Work on longevity has found protective social, cognitive, and emotional factors, but to date we have little understanding of the impact of motivational dynamics. Autonomy orientation, or stable patterns of self-regulation, is theorized to be a protective factor for long-term mental and physical health (Ryan & Deci, 2017), and it is therefore a prime candidate for examining how stable psychosocial factors are linked to longevity, or life expectancy.Method: Essays written in the 1930s by participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
2
7
0
1
Order By: Relevance
“…Several studies chose religious communities as a sample of people living a meaningful and cognitive stimulating life and found that they had a lower risk of Alzheimer’s disease or dementia [ 21 , 22 ]. This corresponds to the findings about the CP’s increased ability to age meaningfully [ 23 ] and findings about their longevity [ 24 , 25 ].…”
Section: Introductionsupporting
confidence: 88%
“…Several studies chose religious communities as a sample of people living a meaningful and cognitive stimulating life and found that they had a lower risk of Alzheimer’s disease or dementia [ 21 , 22 ]. This corresponds to the findings about the CP’s increased ability to age meaningfully [ 23 ] and findings about their longevity [ 24 , 25 ].…”
Section: Introductionsupporting
confidence: 88%
“…In contrast, the frustration of these needs, which occurs when individuals' psychological needs are actively thwarted or blocked (Bartholomew et al, 2011), increases risk for problem behavior and psychopathology (Ryan et al, 2016;Vansteenkiste & Ryan, 2013). Consistent with the dual process model (Vansteenkiste & Ryan, 2013), need satisfaction was found to contribute primarily to individuals' psychological well-being, as indexed by life satisfaction (Tay & Diener, 2011), vitality (Ryan & Deci, 2008), and meaning (Martela et al, 2018) as well as to their physical health, as indexed by increased longevity (Weinstein et al, 2019). In contrast, need frustration relates primarily to ill-being as indexed by symptoms of anxiety, stress, and depression (e.g., Bartholomew et al, 2011;Vandenkerckhove et al, 2020), while also predicting poor physical health, as indexed by poorer sleep quality (Campbell et al, 2017b) and greater stress reactivity (Reeve & Tseng, 2011).…”
Section: Psychological Needsmentioning
confidence: 81%
“…Studies have included measures of somatization and physical symptoms as indicators of ill-being (e.g., Reinboth et al 2004;Reis et al 2000), which were found to stem from low need satisfaction and especially high need frustration. Such findings were corroborated with objective markers of physical functioning, including increased cortisol secretion (Reeve and Tseng 2011), elevated diastolic blood pressure (Weinstein et al 2016b), risk high-density lipoprotein levels (Uysal et al 2020), immunological responses (e.g., Bartholomew et al 2011), and even longevity (Kasser and Ryan 1999;Weinstein et al 2019).…”
Section: Theme 3: What Is the Interplay Between Basic Psychological Amentioning
confidence: 86%